Distribution of Projects Financed by Means of the National Rural Development Programs in Cluj-Napoca Metropolitan Area - MUNTEANU, Gabriela (Studia Universitatis Babeș-Bolyai Geographia, 2024)
Distribution of Projects Financed by means of the National Rural Development Programs in Cluj-Napoca Metropolitan Area. The measures and sub-measures included in the National Rural Development Programs of 2007-2013 and 2014-2020 have also been accessed by the 19 communes of the Cluj-Napoca Metropolitan Area. The present paper focuses on the most significant measures and sub-measures of these programs, in relation to their main purpose (supporting the modernization of agriculture, encouraging the diversification of the rural economy and improving the standard and quality of life in rural areas) and the distribution of contracted projects (and submitted projects - where the case) in this area, an area developing under the socio-economic influence of the nearby city. While for some communes the influence of the city is quite visible, some other communes still preserve accentuated rural features, and these different trajectories are also mirrored in the types of submitted or contracted projects from such communes, in the context of these development programs.